Making sense of science : separating substance from spin - Dean, Cornelia (The Belknap Press of Harvard University Press, 2017)
Cornelia Dean draws on her 30 years as a science journalist with the New York Times to expose the flawed reasoning and knowledge gaps that handicap readers when they try to make sense of science. She calls attention to conflicts of interest in research and the price society pays when science journalism declines and funding dries up.--